К вопросу о защите права общей долевой собственности - Karas, Yekaterina (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the form of co-ownership in the civil law of the Russian Federation. The author present the concept of sharing property right and the problems related to with a special emphasis on the protection of the right to property, vindication and invalidity of transactions.
The protection of the right to property in co-ownership
Keywords: co-ownership; property right; civil law